Implementasi Pembiayaan Murabahah pada Perbankan Syariah di Indonesia: Studi Literatur - Shalahuddin, Muhammad Abdurrahman; Fauziah, Nenden Silmi (Journal of Fiqh in Contemporary Financial Transactions, 2023)
This study tried to look at research related to Murabahah Contract Financing in Islamic Banking in Indonesia bycollecting sufficient information on murabahah contract financing, such as house, vehicle, and productive installments, such as investment and business working capital.  This research  method uses qualitative methods,  namely literature research by collecting some previous research  during the period 2020 (two thousand twenty) to 2022 (two thousand twenty-two) that have been published, journal articles related to murabahah contract financing were collected as many as 25 (twenty-five). The search for this document study is a scientific paper that is not a thesis through the google scholar website page and the help of Public or Perish software (POP) using the keyword "Murabahah Financing". According to Sharia Banking Statistics Data, January 2020 issued by the OJK (Financial Services Authority) on the Composition of   Financing that i provide Sharia People's Financing Banks, jumlah rekening Sharia People's Financing Banks  and equivalent rates of rewards/profit sharing/fees/bonuses of Sharia People's Financing Banks  in the Murabahah Contract it is always the most among other contracts, except in  the equivalent of the level of reward/profit sharing/fee/bonus only slightly difference between the murabahah contract and the musyarakah contract (19.73 with 22.66).  The most research states that murabahah contract financing has a considerable influence on Islamic banking. Based onthe results of this literature study, it can be concluded that murabahah contract financing plays an important role as the most dominant contract used by customers. Penelitian ini mencoba melihat riset terkait Pembiayaan Akad Murabahah pada Perbankan Syariah di Indonesia dengan melakukan pengumpulkan informasi yang cukup terhadap pembiayaan akad murabahah, seperti angsuran rumah, kendaraan, dan produktif, seperti investasi maupun modal kerja usaha. Metode penelitian ini menggunakan metode kualitatif, yaitu penelitian kepustakaan dengan mengumpulkan beberapa penelitian terdahulu selama periode 2020 (dua ribu dua puluh) sampai dengan 2022 (dua ribu dua puluh dua) yang sudah dipublish, artikel jurnal yang terkait pembiayaan akad murabahah dikumpulkan sebanyak 25 (dua puluh lima). Pencarian studi dokumen ini karya tulis ilmiah yang bukan skripsi melalui laman website google scholar dan bantuan software (POP) Public or Perish dengan menggunakan kata kunci “Pembiayaan Murabahah”. Menurut Data Statistik Perbankan Syariah, Januari 2020 terbitan OJK (Otoritas Jasa Keuangan) pada Komposisi Pembiayaan yang diberikan Bank Pembiayaan Rakyat Syariah, jumlah rekening Bank Pembiayaan Rakyat Syariah serta Ekuivalen tingkat imbalan/bagi hasil/fee/bonus Bank Pembiayaan Rakyat Syariah pada Akad Murabahah selalu paling banyak diantara akad lainnya, kecuali pada Ekuivalen tingkat imbalan/bagi hasil/fee/bonus hanya beda sedikit antara akad murabahah dengan akad musyarakah (19,73 dengan 22,66). Penelitian paling banyak menyebutkan bahwa pembiayaan akad murabahah memberikan pengaruh yang cukup besar bagi Perbankan Syariah. Berdasarkan hasil studi literatur ini maka dapat disimpulkan bahwa pembiayaan akad murabahah memegang peranan penting sebagai akad yang paling dominan digunakan oleh Nasabah